2021
DOI: 10.3389/fimmu.2021.728783
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Controls on Epigenetic Reprogramming in Regulatory T Cells

Abstract: Forkhead box protein 3 (Foxp3+)-expressing regulatory T (Treg) cells are a unique CD4+T cell subset that suppresses excessive immune responses. The epigenetic plasticity and metabolic traits of Treg cells are crucial for the acquisition of their phenotypic and functional characteristics. Therefore, alterations to the epigenetics and metabolism affect Treg cell development and function. Recent evidence reveals that altering the metabolic pathways and generation of metabolites can regulate the epigenetics of Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 134 publications
(208 reference statements)
0
11
0
Order By: Relevance
“…These SCFAs may activate Treg under the epithelium of the large intestine. 24,36 Based on this, a detailed investigation of the involvement of PHB in the intestinal microbiota will be necessary in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These SCFAs may activate Treg under the epithelium of the large intestine. 24,36 Based on this, a detailed investigation of the involvement of PHB in the intestinal microbiota will be necessary in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The acetylation status of histones regulates FoxP3 activity. 36 Several reports indicate that 3-HB is an endogenous HDAC inhibitor implicated in intestinal epithelial integrity. 37 In addition, HDAC inhibitors SAHA and trichostatin A have been reported to have Treg-mediated anti-IBD effects, [37][38][39] suggesting that 3-HB produced by PHB degradation functions as an HDAC inhibitor in the intestinal tract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tregs development depends on the key activities of Foxp3, the master-switch transcription factor (Piccirillo 2020 ). Altering the metabolic pathways and generation of metabolites can regulate Tregs (Lu et al 2021 ; W. Wang et al 2021a , b ). Based on the observations in colonic tissues, it was found that butyrate derived from commensal microbes induces Treg differentiation (Braun 2021 ; Furusawa et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of acetyl‐CoA carboxylase 1, the rate‐limiting enzyme for de novo fatty acid synthesis, increases the level of FAO and promotes the development of Treg cells [14]. Moreover, amino acid metabolism enzymes and intermediates are also important factors for the induction of Treg cells [15]. Kynurenine, the metabolite of tryptophan, can bind to aromatic hydrocarbon receptors on T cells and promote Treg cell differentiation [16].…”
Section: Introductionmentioning
confidence: 99%